Evaluation of the strength of the physiological contraction of the leg muscles after the rehabilitation of the knee joint injury of the volleyball - Thabit, H. A.; Shabeeb, H. B.; Al-Badri, M. T. (International Journal of Applied Exercise Physiology, 2019)
This study aims to measure the level of strength of the physiological contraction of the leg muscles one month after the rehabilitation of the knee joint injury for volleyball players. A descriptive design (case study) was used among (59) volleyball players who age 17-19-years-old, one month after finishing the period of physiotherapy for moderate-intensity injuries at the Physiotherapy Hospital at Al-Qanat and Baghdad Teaching Hospital. Data were collected over six-month period. The fixed Dynamometer was used to measure the contraction of the leg muscles at the level of the knee joint from the lateral direction of the medial direction. The bottom of the leg from the area above the foot was stabilized with a loop and pulling the leg towards the thigh backward with stabilizing the left leg on the ground (the test is done by standing). The measurements were applied for six months for each player whose training ages in volleyball ranged from (2-4) years in high school, college, and some sport clubs in Baghdad City. The researchers concluded that it is not possible to rely on the personal experience of the trainer in returning the volleyball players to the stadiums after rehabilitation of their injury unless there is a calendar based on the measurement of the objective devices, and that the weighted standard evaluation achieved (5) levels that can be used to as a parameter of evaluating the Knee joint injuries a month after the completion of rehabilitation programs.